Definitive MPLS network designs - Guichard, Jim (Networking technology series, 2005)
Field-proven MPLS designs covering MPLS VPNs, pseudowire, QoS, traffic engineering, IPv6, network recovery, and multicast Understand technology applications in various service provider and enterprise topologies via detailed design studies Benefit from the authors' vast experience in MPLS network deployment and protocol design Visualize real-world solutions through clear, detailed illustrations Design studies cover various operator profiles including an interexchange carrier (IXC), a national telco deploying a multiservice backbone carrying Internet and IP VPN services as well as national telephony traffic, an international service provider with many POPs all around the globe, and a large enterprise relying on Layer-3 VPN services to control communications within and across subsidiaries Design studies are thoroughly explained through detailed text, sample configurations, and network diagrams Definitive MPLS Network Designs provides examples of how to combine key technologies at the heart of IP/MPLS networks. Techniques are presented through a set of comprehensive design studies. Each design study is based on characteristics and objectives common to a given profile of network operators having deployed MPLS and discusses all the corresponding design aspects. The book starts with a technology refresher for each of the technologies involved in the design studies. Next, a series of design studies is presented, each based on a specific hypothetical network representative of service provider and enterprise networks running MPLS. Each design study chapter delivers four elements. They open with a description of the network environment, including the set of supported services, the network topology, the POP structure, the transmission facilities, the basic IP routing design, and possible constraints. Then the chapters present design objectives, such as optimizing bandwidth usage. Following these are details of all aspects of the network design, covering VPN, QoS, TE, network recovery, and-where applicable-multicast, IPv6, and pseudowire. The chapters conclude with a summary of the lessons that can be drawn from the design study so that all types of service providers and large enterprise MPLS architects can adapt aspects of the design solution to their unique network environment and objectives. Although network architects have many resources for seeking information on the concepts and protocols involved with MPLS, there is no single resource that illustrat...